Development and evaluation of a real-time RT-PCR and a field-deployable RT-insulated isothermal PCR for the detection of Seneca Valley virus - Zhang, Jianqiang (BMC Vet Res, 2019)
BACKGROUND: Seneca Valley virus (SVV) has emerged in multiple countries in recent years. SVV infection can cause vesicular lesions clinically indistinguishable from those caused by other vesicular disease viruses, such as foot-and-mouth disease virus (FMDV), swine vesicular disease virus (SVDV), vesicular stomatitis virus (VSV), and vesicular exanthema of swine virus (VESV). Sensitive and specific RT-PCR assays for the SVV detection is necessary for differential diagnosis. Real-time RT-PCR (rRT-PCR) has been used for the detection of many RNA viruses. The insulated isothermal PCR (iiPCR) on a portable POCKIT™ device is user friendly for on-site pathogen detection. In the present study, SVV rRT-PCR and RT-iiPCR were developed and validated. RESULTS: Neither the SVV rRT-PCR nor the RT-iiPCR cross-reacted with any of the vesicular disease viruses (20 FMDV, two SVDV, six VSV, and two VESV strains), classical swine fever virus (four strains), and 15 other common swine viruses. Analytical sensitivities of the SVV rRT-PCR and RT-iiPCR were determined using serial dilutions of in vitro transcribed RNA as well as viral RNA extracted from a historical SVV isolate and a contemporary SVV isolate. Diagnostic performances were further evaluated using 125 swine samples by two approaches. First, nucleic acids were extracted from the 125 samples using the MagMAX™ kit and then tested by both RT-PCR methods. One sample was negative by the rRT-PCR but positive by the RT-iiPCR, resulting in a 99.20% agreement (124/125; 95% CI: 96.59–100%, κ = 0.98). Second, the 125 samples were tested by the taco™ mini extraction/RT-iiPCR and by the MagMAX™ extraction/rRT-PCR system in parallel. Two samples were positive by the MagMAX™/rRT-PCR system but negative by the taco™ mini/RT-iiPCR system, resulting in a 98.40% agreement (123/125; 95% CI: 95.39–100%, κ = 0.97). The two samples with discrepant results had relatively high C(T) values. CONCLUSIONS: The SVV rRT-PCR and RT-iiPCR developed in this study are very sensitive and specific and have comparable diagnostic performances for SVV RNA detection. The SVV rRT-PCR can be adopted for SVV detection in laboratories. The SVV RT-iiPCR in a simple field-deployable system could serve as a tool to help diagnose vesicular diseases in swine at points of need.